Investigating the Relationship Between Total Quality Management and Primary School Academic Performance with Innovation as a Mediator Using SEM - Alhosani, Mohamed Salem Ahmed Ibrahim; Yaakub, Kamarul Bahari (European Journal of Economics and Business Studies, 2021)
This study aims to examine the relationship between TQM (TQM) and primary school academic performance in Abu Dhabi with innovation as a mediator using SEM. A quantitative research design was utilized. A total of 342 teachers were chosen as a sample through quota and simple sampling technique. Data analysis using structural equation modeling was used. The results revealed that there was significant relationship between TQM and primary school academic performance was -0.50; significant relationship found between TQM and innovation. The further found that significant relationship was exist between innovation and primary school academic performance was 0.1.51 while TQM has significant relationship with innovation with .92. The result also found that innovation mediate on the relationship between TQM and primary school academic performance with partial mediation. It is hope of this study that TQM would be used by schools in Abu Dhabi region to improve primary schools’ academic performance. The implication of this study suggested that TQM should be internalize and use it to improve primary school academic performance in Abu Dhabi. However, a further investigation should be examining into the role the TQM play on primary school academic performance.
Keywords: TQM, Innovation, Primary School Academic Performance, Education, School